2021
DOI: 10.1111/jnc.15383
|View full text |Cite
|
Sign up to set email alerts
|

Activation of spinal PDGFRβ in microglia promotes neuronal autophagy via p38 MAPK pathway in morphine‐tolerant rats

Abstract: Morphine is the most potent analgesic in clinical treatment for various painful conditions. Long-term usage of morphine inevitably leads to the development of antinociceptive tolerance, which limits its clinical utilization (Christie, 2008;Wickham, 2017). For several decades, numerous studies have been devoted to illuminating the mechanisms underlying morphine tolerance, including nitric oxide-cyclic 3'-5' guanosine monophosphate signaling pathway, α 2 noradrenergic system cannabinoid system, and hyperexcitabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…These results provide some details of the mechanistic basis of the neuroinflammatory process that may be important in migraine pathogenesis and evidence that this process can be mediated by microglia autophagy 58 . The importance of P38 MAPK‐mediated autophagy in microglia was confirmed in morphine‐tolerant rats 59 . Upregulation of P2X4R and BDNF as well as an increase in phosphorylated extracellular regulated protein kinases and CGRP release in the TNC in a chronic migraine NTG‐induced animal model 47 .…”
Section: Neurons’ Interplay With Microglia In Migraine Pathogenesismentioning
confidence: 71%
See 1 more Smart Citation
“…These results provide some details of the mechanistic basis of the neuroinflammatory process that may be important in migraine pathogenesis and evidence that this process can be mediated by microglia autophagy 58 . The importance of P38 MAPK‐mediated autophagy in microglia was confirmed in morphine‐tolerant rats 59 . Upregulation of P2X4R and BDNF as well as an increase in phosphorylated extracellular regulated protein kinases and CGRP release in the TNC in a chronic migraine NTG‐induced animal model 47 .…”
Section: Neurons’ Interplay With Microglia In Migraine Pathogenesismentioning
confidence: 71%
“…58 The importance of P38 MAPK-mediated autophagy in microglia was confirmed in morphine-tolerant rats. 59 Upregulation of P2X4R and BDNF as well as an increase in phosphorylated extracellular regulated protein kinases and CGRP release in the TNC in a chronic migraine NTG-induced animal model. 47 Repeated administration of IVM, a P2X4R agonist, increased the levels of phosphorylated protein kinases, including p38 MAPK and CGRP release in the TNC.…”
Section: Neuron S' Interpl Ay With MI Crog Lia In Mig R Aine Pathog E...mentioning
confidence: 99%
“…Our research contributes to this area by suggesting that MTD treatment may exacerbate oxidative imbalance while also potentially enhancing antioxidant defense mechanisms. Additionally, we observed that morphine modulates synapses via ROS, instigating the activation of pathways related to endoplasmic reticulum stress, autophagy, and apoptosis 76–78 …”
Section: Discussionmentioning
confidence: 89%
“…In the morphine tolerance model, TRPV1 increased, and when phosphorylated MAPK was inhibited, TRPV1 decreased correspondingly, suggesting that MAPK played a certein regulatory role in morphine induced by TRPV1 ( Chen et al, 2008 ). Studies have also shown that chronic morphine administration can activate platelet-derived growth factor receptor-β (PDGFRβ) signaling, which is a specific mediator that regulates opioid tolerance (Li [a] et al, 2020; Jia et al, 2021 ). Morphine treatment activates PDGFRβ, and PDGFRβ induces the activation and expression of HSP27 via the p38/MAPK and PI3K/Akt signaling pathways.…”
Section: Mechanisms Of Opioid/morphine Tolerancementioning
confidence: 99%
“…PGDFRβ-mediated HSP27 activation participates in morphine tolerance ( Li et al, 2020 ). In a model of morphine tolerance in rats, activating PDGFR in spinal microglia induced autophagy in GABAergic neurons via the p38/MAPK pathway, and autophagy inhibition attenuated the development of morphine tolerance ( Jia et al, 2021 ). The detailed mechanisms of PDGFR and autophagy deserve further exploration.…”
Section: Mechanisms Of Opioid/morphine Tolerancementioning
confidence: 99%